THE DIFFERENCES OF PROTEIN 53 EXPRESSION IN OVARIAN EPITHELIAL TUMOR BENIGN, BORDERLINE AND MALIGNANT TYPE - Mega Putra, I Gede (E-Journal Obstetric & Gynecology Udayana, 2014)
Ovarian tumor is a gynecologic oncology problemthroughoutthe worldand is thefifthcause of deathfrom cancerin women. Ovarian tumor classification into benignepithelial ovariantumors, borderlineandmalignanthas causeddifficulties inits management, especially for borderlinetypein young womenwhostillwant to preservetheir reproductivefunction. Variousstudies have been conductedtofindamarkerthatcan beusedforearly detection, prognosisandguidanceinits management,which are expected todecreasemorbidity andmortalityandimprove survival. Therefore, someresearchers performedgeneticapproach torevealthe occurrence ofthetumoretiopathogenesis. One of the genesthat play a rolein the occurrence ofatumorisP53whichis a genethat expressesa protein53(p53).The purpose ofthis study wastodeterminethe expression ofp53andthe differenceintypesof epithelial ovariantumorsbenign, borderlineandmalignant. This was a cross-sectional study in Obstetrics and Gynecology, Pathology Anatomy and Medical Records Departments of Sanglah Central Public Hospital Denpasar, which was conducted from July 2011 until December 2013 with sample of 49 paraffin blocks pieces. Paraffin block samples were grouped based on the type of epithelial ovarian tumors which are benign, borderline and malignant. Eachgroupof tumortypes was then examined for its p53 expressionbyimmunohistochemical technique. Furthermore, the differencesbetweenbenignepithelial ovariantumors, borderlineandmalignant were determined usingChi-Square test. The averages ofage, Body Mass Index(BMI), parity, andhistory ofhormonal contraceptionin all threetypesof epithelial ovariantumors groups werehomogeneous. P53 expression in ovarian epithelial tumor was 6,25% in benign type, 15,38% in borderline type, and 40% in malignant type. Based on Chi square test, there was a significant difference in p53 expression between the benign epithelial ovarian tumor and malignant type (p=0,024), no significant difference in p53 expression between the benign type and borderline type (p=0,448), and no significant difference in p53 expression between the borderline type and the malignant type (p=0,202). Â Key word : p53 expression, benign epithelial ovarian tumor, borderline and malignant type.